Predicting army reserve unit manning using market demographics. Issue 2 (7th November 2018) - Parker, Nathan; Alt, Jonathan; Buttrey, Samuel; House, Jeffrey
Abstract : Purpose: This research develops a data-driven statistical model capable of predicting a US Army Reserve (USAR) unit staffing levels based on unit location demographics. This model provides decision makers an assessment of a proposed station location's ability to support a unit's personnel requirements from the local population. Design/methodology/approach: This research first develops an allocation method to overcome challenges caused by overlapping unit boundaries to prevent over-counting the population. Once populations are accurately allocated to each location, we then then develop and compare the performance of statistical models to estimate a location's likelihood of meeting staffing requirements. Findings: This research finds that local demographic factors prove essential to a location's ability to meet staffing requirements. We recommend that the USAR and US Army Recruiting Command (USAREC) use the logistic regression model developed here to support USAR unit stationing decisions; this should improve the ability of units to achieve required staffing levels. Originality/value: This research meets a direct request from the USAREC, in conjunction with the USAR, for assistance in developing models to aid decision makers during the unit stationing process.